A one-pot synthesized degradable copolyester and preparation method thereof

Through the one-pot synthesis method, PET-PCL random copolyester is prepared using raw materials such as ε-caprolactone and terephthalic acid, which solves the difficulty of existing degradable polyester materials to have both degradability and thermal processing properties. The problem of this achieves efficient and economical material preparation and application.

CN116262814BActive Publication Date: 2025-02-07ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310056242.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-18
Publication Date
2025-02-07
Estimated Expiration
2043-01-18

AI Technical Summary

Technical Problem

The existing degradable polyester materials are difficult to have both degradability and good thermal processing properties, which leads to problems such as environmental pollution and high production costs in their applications.

Method used

By synthesizing by one pot method, ε-caprolactone is used as a degradable monomer, and pre-loop-opening polymerization is used to form double-ended hydroxyl-terminated polycaprolactone (PCL), and then copolymerize with terephthalic acid and ethylene glycol. PET-PCL random copolyester was prepared, which had good degradability and thermal processing properties.

Benefits of technology

It realizes that PET-PCL copolyester has good degradability and thermal processing performance, reducing equipment investment and production costs, and improving the degradation performance of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004060589440000071
    Figure BDA0004060589440000071
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of degradable copolyesters, and discloses a degradable copolyester synthesized by a one-pot method and a preparation method thereof. The preparation method comprises the following steps: subjecting (-caprolactone to a ring-opening polymerization reaction to obtain a polymerization product; then adding terephthalic acid and ethylene glycol to carry out an esterification reaction to obtain an esterification product; then adding a catalyst, a stabilizer and a branching agent to carry out a condensation polymerization reaction to obtain a degradable copolyester. The invention uses (-caprolactone as a degradable monomer, pre-ring-opening polymerization to generate a double-terminal hydroxyl-terminated polycaprolactone, and then prepares a PET-PCL random copolyester by a one-pot method, which has good degradability; the PCL chain segment has a high thermal decomposition temperature and certain flexibility, can effectively reduce the glass transition temperature of PETCL, so that it has good heat resistance and thermal processing performance, and has a high monomer utilization rate, and the prepared copolyester does not need post-treatment, and the equipment investment is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of degradable copolyester, in particular to a degradable copolyester synthesized by a one-pot method and a preparation method thereof. Background Art

[0002] With the development of the petroleum industry, a large number of small molecular monomers from petroleum cracking are polymerized to form high-strength, lightweight and low-cost polymer materials. Once polymer materials came out, they were quickly applied to various fields such as national defense, industry, agriculture, medicine, construction and food, and have gradually replaced wood and metal materials and become an indispensable part of human life.

[0003] At present, polyester material is one of the most consumed synthetic polymers in the world, and it has good stability. However, as the global use of polyester materials increases year by year, related waste is randomly discarded on land and in the ocean, and the degradation rate of polyester materials is very low. After long-term accumulation, it has caused serious environmental pollution and damage to the ecosystem. Some polyester materials are broken down into microplastics under the action of organisms, sunlight and water, and enter the human body through the food chain, endangering human health. In order to reduce the pollution of polyester materials to the human living environment, degradable polyesters have become a hot research direction today. Currently known polyesters include polyglycolic acid (PGA), polylactic acid (PLA), polyvalerolactone (PVL), polycaprolactone (PCL), polyhydroxyalkanoate (PHA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), etc.

[0004] Polyethylene terephthalate (PET) is the most widely used synthetic polyester today. Its excellent mechanical properties and anti-aging properties make it widely used in packaging, automobile, construction, textile and other industries. However, due to the high regularity and crystallinity of PET molecular chains, it is difficult to degrade in the natural state, and its waste exists in the natural environment for a long time, forming pollution. Therefore, by introducing biodegradable and heat-stable aliphatic polyester PCL, the copolyester obtained will be endowed with degradability and good thermal processing properties, further expanding the application of PET copolyester.

[0005] A Chinese invention patent with publication number CN114292388A discloses a method for preparing a degradable PET-based copolyester, which uses glycolic acid, terephthalic acid and ethylene glycol to copolymerize to obtain a modified PET containing a rapidly degradable PGA segment. However, PGA is easily decomposed at high temperatures, which seriously affects its thermal processability.

[0006] A Chinese invention patent with publication number CN104312107A discloses a degradable modified PET material and a preparation method thereof. PET is chemically blended with isosorbide-maleic anhydride polyester through a coupling agent hexamethylene diisocyanate to prepare modified PET, but the degradation of the PET chain cannot be achieved.

[0007] Chinese invention patent with publication number CN1204654A discloses a method for synthesizing biodegradable copolyester, which uses bis(hydroxyethyl) terephthalate and caprolactone as raw materials, but the post-processing is relatively complicated, which increases the cost of industrial production. Summary of the invention

[0008] In order to solve the technical problem that degradable polyester cannot have both degradability and good thermal processing properties, the present invention provides a degradable copolyester synthesized by a one-pot process and a preparation method thereof, wherein ε-caprolactone is used as a degradable monomer and pre-ring-polymerized to generate double-end hydroxyl-terminated polycaprolactone, and then the PET-PCL random copolyester is prepared by a one-pot process, so that it has both good degradability and thermal processing properties.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] In the first aspect, the present invention provides a method for preparing a degradable copolyester synthesized in one pot, comprising the following steps: subjecting ε-caprolactone to a ring-opening polymerization reaction to obtain a polymerization product; then adding terephthalic acid and ethylene glycol to carry out an esterification reaction to obtain an esterification product; then, adding a catalyst I, a stabilizer and a branching agent to carry out a condensation reaction to obtain a degradable copolyester.

[0011] The present invention uses ε-caprolactone as a degradable monomer, pre-ring-opening polymerizes it to generate double-end hydroxyl-terminated polycaprolactone (PCL), then copolymerizes it with terephthalic acid and ethylene glycol, and then esterifies it with ethylene glycol and terephthalic acid. Then, a condensation reaction is carried out in a high-temperature and high-vacuum environment with the addition of a catalyst, a stabilizer and a branching agent, so as to realize a one-pot method for preparing a degradable copolyester.

[0012] PCL is biodegradable. PET-PCL random copolyester (PETCL) is prepared through ester exchange reaction, which can effectively reduce the crystallinity and increase the content of amorphous molecular chains, thereby increasing the volume of loose amorphous regions in the crystal structure, which is conducive to the entry of oxygen and water into the molecular chain, making the copolyester more degradable. The degradable PCL segment has a high thermal decomposition temperature (350°C) and a certain flexibility, which can effectively reduce the glass transition temperature of PETCL, making PETCL have good heat resistance and thermal processing properties. Since ε-caprolactone is pre-polymerized before the esterification reaction process, the monomer utilization rate is high, the prepared PETCL copolyester does not require post-treatment, and the equipment investment is relatively small.

[0013] Preferably, the ring-opening polymerization reaction is: ε-caprolactone, catalyst II and water are mixed, and the ring-opening polymerization reaction occurs at 100-160° C. and normal pressure under the action of the catalyst for 2-6 hours.

[0014] ε-caprolactone was preliminarily treated with water as an initiator and ring-opening polymerization was carried out under the action of a catalyst to obtain long-chain PCL.

[0015] Preferably, the catalyst II is one or more of dibutyltin dilaurate, dioctyltin dilaurate and stannous octoate, and the amount of tin element added to the catalyst accounts for 50 to 200 ppm of the mass of ε-caprolactone.

[0016] Preferably, the molar proportion of ε-caprolactone in the total of ε-caprolactone and terephthalic acid is 30-70%, and further preferably, the molar proportion of ε-caprolactone in the total of ε-caprolactone and terephthalic acid is 50-70%; the molar ratio of ethylene glycol to terephthalic acid is 1.1-3:1.

[0017] By adjusting the molar ratio of ε-caprolactone to terephthalic acid, the content of branching agent and the polymerization reaction time, a copolyester with a melt index of 5.0-20.0 and controllable molecular weight is obtained without chain extension and viscosity increase, further reducing production processes and equipment investment.

[0018] Preferably, the esterification reaction is carried out at 220-260° C. and a nitrogen pressure of 0-50 kPa for 2-6 hours.

[0019] Preferably, the polycondensation reaction is carried out at 270-290° C. and in a vacuum environment below 80 Pa for 1-3 hours.

[0020] Preferably, the catalyst I is tetrabutyl titanate, wherein the added amount of titanium element is 1 to 30 ppm based on the mass of the degradable copolyester.

[0021] Since the polycondensation catalyst is sensitive to water, the esterification rate should be greater than 95% before adding it during the polycondensation reaction to avoid the influence of water produced during the esterification process.

[0022] Preferably, the stabilizer is one or more of phosphoric acid, trimethyl phosphate, triethyl phosphate and triphenyl phosphate, and the added amount of the stabilizer accounts for 20 to 100 ppm of the mass of the degradable copolyester.

[0023] In a second aspect, the present invention also provides a degradable copolyester prepared by the above preparation method.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) ε-caprolactone is used as a degradable monomer, and a double-end hydroxyl-terminated polycaprolactone (PCL) is prepared by a one-pot method to obtain PET-PCL random copolyester (PETCL), which has good degradability;

[0026] (2) PCL segments have a high thermal decomposition temperature (350°C) and certain flexibility, which can effectively reduce the glass transition temperature of PETCL, making PETCL have good heat resistance and thermal processing properties;

[0027] (3) Since ε-caprolactone is prepolymerized before the esterification process, the monomer utilization rate is high, the prepared PETCL copolyester does not require post-treatment, and the equipment investment is relatively small;

[0028] (4) By adjusting the molar ratio of ε-caprolactone to terephthalic acid, the content of branching agent and the polymerization reaction time, a copolyester with a high melt index and controllable molecular weight is obtained without the need for chain extension and viscosity increase, further reducing the production process and equipment investment. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0030] Example 1

[0031] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 30:70):

[0032] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 100 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 120° C. under normal pressure for 3 hours to obtain a polymer product PCL;

[0033] (2) adding terephthalic acid and ethylene glycol (the molar amount of which is 1.5 times the molar equivalent of terephthalic acid), mixing evenly, and reacting for 4 hours at 245° C. and 40 kPa of nitrogen atmosphere to obtain an esterified product;

[0034] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, tetrabutyl titanate (the titanium element of which accounts for 20 ppm of the mass of the degradable copolyester) and trimethyl phosphate (the amount of which accounts for 60 ppm of the mass of the degradable copolyester) are added, and a polycondensation reaction is carried out under vacuum conditions of 280° C. and 30 Pa for 1.5 hours to obtain a degradable copolyester.

[0035] Example 2

[0036] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 50:50):

[0037] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 120 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 125° C. under normal pressure for 4 hours to obtain a polymer product PCL;

[0038] (2) adding terephthalic acid and ethylene glycol (the molar amount of which is 1.8 times the molar equivalent of terephthalic acid), mixing evenly, and reacting for 5 hours at 240° C. and 35 kPa of nitrogen atmosphere to obtain an esterified product;

[0039] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, tetrabutyl titanate (the titanium element of which accounts for 22 ppm of the mass of the degradable copolyester) and triethyl phosphate (the amount of which accounts for 50 ppm of the mass of the degradable copolyester) are added, and a polycondensation reaction is carried out under vacuum conditions of 275° C. and 25 Pa for 2 hours to obtain a degradable copolyester.

[0040] Example 3

[0041] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 70:30):

[0042] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 135 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 140° C. under normal pressure for 4.5 hours to obtain a polymer product PCL;

[0043] (2) adding terephthalic acid and ethylene glycol (the molar amount of which is twice the molar equivalent of terephthalic acid), mixing them evenly, and reacting them for esterification at 230° C. and 30 kPa of nitrogen atmosphere for 5 hours to obtain an esterified product;

[0044] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, tetrabutyl titanate (the titanium element of which accounts for 24 ppm of the mass of the degradable copolyester) and triphenyl phosphate (the amount of which accounts for 53 ppm of the mass of the degradable copolyester) are added, and a polycondensation reaction is carried out under vacuum conditions of 270° C. and 23 Pa for 2.5 hours to obtain a degradable copolyester.

[0045] Example 4

[0046] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 60:40):

[0047] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 135 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 135° C. under normal pressure for 4 hours to obtain a polymer product PCL;

[0048] (2) adding terephthalic acid and ethylene glycol (the molar amount of which is 1.9 times the molar equivalent of terephthalic acid), mixing evenly, and reacting for 4.5 hours at 235° C. and 32 kPa of nitrogen atmosphere to obtain an esterified product;

[0049] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, tetrabutyl titanate (the titanium element of which accounts for 23 ppm of the mass of the degradable copolyester) and triphenyl phosphate (the amount of which accounts for 52 ppm of the mass of the degradable copolyester) are added, and a polycondensation reaction is carried out under vacuum conditions of 272° C. and 25 Pa for 2.2 hours to obtain a degradable copolyester.

[0050] Comparative Example 1

[0051] The difference from Example 1 is that the amount of ε-caprolactone added is too small.

[0052] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 5:95):

[0053] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 100 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 120° C. under normal pressure for 3 hours to obtain a polymer product PCL;

[0054] (2) adding terephthalic acid and ethylene glycol (the molar amount of which is 1.5 times the molar equivalent of terephthalic acid), mixing evenly, and reacting for 4 hours at 245° C. and 40 kPa of nitrogen atmosphere to obtain an esterified product;

[0055] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, tetrabutyl titanate (the titanium element of which accounts for 20 ppm of the mass of the degradable copolyester) and trimethyl phosphate (the amount of which accounts for 60 ppm of the mass of the degradable copolyester) are added, and a polycondensation reaction is carried out under vacuum conditions of 280° C. and 30 Pa for 1.5 hours to obtain a degradable copolyester.

[0056] Comparative Example 2

[0057] The difference from Example 2 is that the added amount of ε-caprolactone is too large.

[0058] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 90:10):

[0059] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 120 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 125° C. under normal pressure for 4 hours to obtain a polymer product PCL;

[0060] (2) adding terephthalic acid and ethylene glycol (the molar amount of which is 1.8 times the molar equivalent of terephthalic acid), mixing evenly, and reacting for 5 hours at 240° C. and 35 kPa of nitrogen atmosphere to obtain an esterified product;

[0061] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, tetrabutyl titanate (the titanium element of which accounts for 22 ppm of the mass of the degradable copolyester) and triethyl phosphate (the amount of which accounts for 50 ppm of the mass of the degradable copolyester) are added, and a polycondensation reaction is carried out under vacuum conditions of 275° C. and 25 Pa for 2 hours to obtain a degradable copolyester.

[0062] Comparative Example 3

[0063] The difference from Example 3 is that a branching agent is added.

[0064] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 70:30):

[0065] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 135 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 140° C. under normal pressure for 4.5 hours to obtain a polymer product PCL;

[0066] (2) adding terephthalic acid and ethylene glycol (the molar amount of which is twice the molar equivalent of terephthalic acid), mixing them evenly, and reacting them for esterification at 230° C. and 30 kPa of nitrogen atmosphere for 5 hours to obtain an esterified product;

[0067] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, tetrabutyl titanate (the titanium element of which accounts for 24 ppm of the mass of the degradable copolyester), triphenyl phosphate (the amount of which accounts for 53 ppm of the mass of the degradable copolyester) and pentaerythritol (the amount of which accounts for 300 ppm of the mass of the degradable copolyester) are added, and a polycondensation reaction is carried out under vacuum conditions of 270° C. and 23 Pa for 2.5 hours to obtain a degradable copolyester.

[0068] Comparative Example 4

[0069] The difference from Example 3 is that the time of the ring-opening polymerization is too long.

[0070] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 70:30):

[0071] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 135 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 140° C. under normal pressure for 7.5 hours to obtain a polymer product PCL;

[0072] (2) adding terephthalic acid and ethylene glycol (the molar amount of which is twice the molar equivalent of terephthalic acid), mixing them evenly, and reacting them for esterification at 230° C. and 30 kPa of nitrogen atmosphere for 5 hours to obtain an esterified product;

[0073] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, tetrabutyl titanate (the titanium element of which accounts for 24 ppm of the mass of the degradable copolyester), triphenyl phosphate (the amount of which accounts for 53 ppm of the mass of the degradable copolyester) and pentaerythritol (the amount of which accounts for 300 ppm of the mass of the degradable copolyester) are added, and a polycondensation reaction is carried out under vacuum conditions of 270° C. and 23 Pa for 2.5 hours to obtain a degradable copolyester.

[0074] Comparative Example 5

[0075] The difference from Example 4 is that the ε-caprolactone is not pre-ring-opening polymerized.

[0076] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 60:40):

[0077] (1) adding purified and dehydrated ε-caprolactone, terephthalic acid and ethylene glycol (the molar amount of which is 1.9 times the molar equivalent of terephthalic acid) into a reactor, mixing them evenly, and then carrying out an esterification reaction at 230° C. and 50 kPa of nitrogen atmosphere for 6 hours to obtain an esterified product; (2) when the esterification rate of the esterification reaction in step (1) is greater than 95%, adding tetrabutyl titanate (the titanium element of which is 30 ppm of the mass of the degradable copolyester) and triphenyl phosphate (the amount of which is 60 ppm of the mass of the degradable copolyester) and carrying out a polycondensation reaction at 275° C. and 10 Pa of vacuum conditions for 4 hours to obtain a degradable copolyester.

[0078] Comparative Example 6

[0079] The difference from Example 4 is that a polycondensation catalyst is added before the esterification reaction.

[0080] Preparation of PETCL copolyester (molar ratio of ε-caprolactone and terephthalic acid is 60:40):

[0081] (1) adding purified and dehydrated ε-caprolactone and stannous octoate (wherein the tin element accounts for 135 ppm of the mass of the ε-caprolactone monomer) into a reactor, and performing ring-opening polymerization at 135° C. under normal pressure for 4 hours to obtain a polymer product PCL;

[0082] (2) adding terephthalic acid, ethylene glycol (its molar amount is 1.9 times the molar equivalent of terephthalic acid) and tetrabutyl titanate (its titanium element accounts for 23 ppm of the mass of the degradable copolyester), mixing them evenly, and then reacting them for esterification for 4.5 hours under a nitrogen atmosphere of 235° C. and 32 kPa to obtain an esterified product;

[0083] (3) When the esterification rate of the esterification reaction in step (2) is greater than 95%, triphenyl phosphate is added (the amount of which is 52 ppm based on the mass of the degradable copolyester), and a polycondensation reaction is carried out under vacuum conditions of 272° C. and 25 Pa for 2.2 hours to obtain the degradable copolyester.

[0084] Performance Testing

[0085] The glass transition temperature (T g )、Melting point (T m ), melt mass flow rate (MFR), tensile strength and 180-day composting degradation rate tests. The results are shown in Table 1.

[0086] The T of copolyester was measured by differential scanning calorimetry. g and T m ;

[0087] MFR is tested using a melt indexer according to GB / T 3682.1-2018;

[0088] Test tensile strength according to GB / T 1040-2018;

[0089] The 180-day composting degradation rate was tested according to GB / T 19277.2-2013.

[0090] Table 1 T of PETCL copolyester g , T m , MFR, tensile strength and 180-day composting degradation rate

[0091]

[0092] From Table 1, we can see that:

[0093] (1) Comparison between Comparative Example 1 and Example 1 shows that compared with the case where too low a content of ε-caprolactone is added, the regularity of the molecular chain of the copolyester in Example 1 is destroyed, the glass transition temperature is reduced, two melting points appear, the melt mass flow rate is slightly increased, and the processing capacity is enhanced. Due to the increase in the amount of degradable monomer added, the degradation performance of the copolyester is improved.

[0094] (2) Comparison between Comparative Example 2 and Example 2 shows that compared with the copolyester with too high a content of ε-caprolactone, the melting enthalpy corresponding to the PCL and PET polymer chains in Example 2 is smaller, and the melt mass flow rate is significantly increased. When sufficient ε-caprolactone is added, the degradation performance of the PETCL copolyester can be effectively guaranteed. At this time, the degradation rate of Example 2 is relatively high, which may be attributed to the high randomness of the copolyester. The copolyester obtained in Comparative Example 2, even though the degradation rate is relatively high, has seriously lost the mechanical properties of the copolyester, and the tensile strength is only 16.4 MPa.

[0095] (3) Comparison between Comparative Example 3 and Example 3 shows that compared with the copolyester without adding a branching agent, the melt mass flow rate in Comparative Example 3 is reduced and the tensile strength is increased, while the increase in the crosslinking degree of the copolyester leads to a decrease in the degradation rate and a decrease in the processing performance.

[0096] (4) Comparison between Example 4 and Example 3 shows that for the copolyester with too long ring-opening polymerization time of ε-caprolactone, the molecular weight of the pre-polymerized PCL increases, the molecular chain grows, the efficiency of participating in the ester exchange reaction decreases, and the melting enthalpy of the PCL chain in the PETCL copolyester increases, resulting in reduced randomness, reduced degradation rate, slightly reduced melt mass flow rate, and slightly increased tensile strength. Therefore, the melt mass flow rate of the copolyester can be regulated by adjusting the ring-opening polymerization time.

[0097] (5) Comparison between Example 5 and Example 4 shows that compared with the co-esterification process of ε-caprolactone, ethylene glycol and terephthalic acid, due to the high degree of ester exchange of polycaprolactone in the polycondensation process, the pre-ring opening-co-esterification method can simplify the post-treatment process and reduce equipment investment. At the same time, the performance of the copolyester obtained is better than that of the co-esterification process.

[0098] (6) Comparison between Comparative Example 6 and Example 4 shows that compared with the copolyester in which the polycondensation catalyst is added before the esterification process, the copolyester in which the polycondensation catalyst is added during the polycondensation process can effectively avoid the hydrolysis of the catalyst and ensure its catalytic activity. The PETCL copolyester prepared in Comparative Example 6 has a lower molecular weight, a higher melt mass flow rate, and a lower tensile strength, which is attributed to the hydrolysis of the polycondensation catalyst. The reduced catalytic activity seriously affects the mechanical properties of the copolyester.

[0099] By adopting the method of the present invention, a copolyester with a high melt mass flow rate and controllable molecular weight can be prepared by controlling the ring-opening reaction time, the polycondensation reaction time and the branching agent content, without further solid phase viscosity enhancement, thereby further reducing production costs and equipment investment.

[0100] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a degradable copolyester synthesized by a one-pot process, characterized in that: The method comprises the following steps: subjecting the purified and dehydrated e-caprolactone to a ring-opening polymerization reaction at 100-160°C and normal pressure under the action of a catalyst II for 2-6 hours, wherein the molar proportion of e-caprolactone in the total amount of e-caprolactone and terephthalic acid is 30-70%, thereby obtaining a polymerization product; then, terephthalic acid and ethylene glycol are added to carry out an esterification reaction, wherein the molar ratio of ethylene glycol to terephthalic acid is 1.1-3:1, thereby obtaining an esterification product; and then, a catalyst I and a stabilizer are added to carry out a polycondensation reaction, thereby obtaining a degradable copolyester.

2. The method for preparing a degradable copolyester synthesized by one-pot method according to claim 1, characterized in that: The catalyst II is one or more of dibutyltin dilaurate, dioctyltin dilaurate and stannous octoate, and the amount of tin element added to the catalyst accounts for 50-200 ppm of the mass of e-caprolactone.

3. The method for preparing a degradable copolyester synthesized by one-pot method according to claim 1, characterized in that: The esterification reaction is as follows: the esterification reaction occurs at 220-260°C and a nitrogen pressure of 0-50 kPa for 2-6 hours.

4. The method for preparing a degradable copolyester synthesized by one-pot method according to claim 1, characterized in that: The polycondensation reaction is as follows: the polycondensation reaction occurs at 270-290°C and in a vacuum environment below 80 Pa for 1-3 hours.

5. The method for preparing a degradable copolyester synthesized by a one-pot process as claimed in claim 1 or 4, characterized in that: The catalyst I is tetrabutyl titanate, wherein the added amount of titanium element accounts for 1-30 ppm of the mass of the degradable copolyester.

6. The method for preparing a degradable copolyester synthesized by a one-pot process as claimed in claim 1 or 4, characterized in that: The stabilizer is one or more of phosphoric acid, trimethyl phosphate, triethyl phosphate and triphenyl phosphate, and the added amount of the stabilizer accounts for 20-100 ppm of the mass of the degradable copolyester.

7. The method for preparing a degradable copolyester synthesized by one-pot method according to claim 1, characterized in that: When the esterification rate of the esterification reaction is greater than 95%, catalyst I and stabilizer are added to carry out polycondensation reaction.

8. A degradable copolyester prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Degradable modified PET material and preparation method thereof

    CN104312107A

  • Preparation method of degradable PET-based copolyester

    CN114292388A

  • Method of synthesis for biodegradable copolyester

    CN1204654A

  • Copolyester and preparation method thereof

    CN103724606A